2002: The Israelites of Now - Espinoza-Benavides Joyo, Enrique (2005)
In the present work I will deal with the religious group "Evangelical Association of the Israelite Mission of the New Universal Pact" (AEMINPU) in two moments: a) During the creation, expansion and death of the religious leader, b) Situation of the religious group after the physical death of the leader.